Hard Fighting Israel in Lebanon and Gaza - Johnson, David E. (RAND Corporation, 2011)
Like Israel in 2006, the United States today is likely ill prepared for hybrid warfare. To identify lessons that the U.S. military might learn from the Israeli experience in Lebanon, the author examines the state of the Israeli military before the Second Lebanon War, the lessons it learned during that conflict, the reforms it undertook to address its deficiencies, and how it fared during Operation Cast Lead three years later.